Ethnic diversity and inclusiveness among medical residents in the Netherlands: results from a single-centered survey study - Linda Al-Hassany; Rianne J. Zaal; Karen M. Stegers-Jager; Adrienne A. M. Zandbergen (BMC Medical Education)
Abstract Purpose of study Despite the recognized importance of an ethnically diverse healthcare workforce, the current population of medical specialists does not adequately reflect our society. To further unravel how and at which stages of the career path such diversity loss occurs, we studied ethnic diversity and perceptions of inclusiveness among medical residents. Materials and methods We conducted a cross-sectional study among all residents of Erasmus Medical Center in the highly multicultural city of Rotterdam, the Netherlands. An online survey was distributed, in which we inquired about (i) ethnic diversity and (ii) perceptions of inclusivity. The latter outcome includes sense of belonging to the team of supervisors, measured by perceived level of resemblance between residents and their supervisor(s), while focusing on ethnic, cultural, and socioeconomic levels. Residents from different specialties were divided into four groups, according to their medical specialty, i.e., surgical specialties, internal medicine specialties, overall diagnostic/supportive specialties, and family medicine & intellectual disability medicine. Descriptive statistics were applied. Results From the total of 986 invited residents, 493 (50.0%) participated (median age 32 years [IQR 30–34]), consisting of 346 (70.2%) females. Results showed that the majority, 335 (68.2%) were of Dutch origin, 90 (18.3%) were children of migrants, and 66 (13.4%) were migrants. We observed notable differences across medical specialties, with the highest degree of ethnic diversity in surgical specialties. Except for residents from supportive specialties, residents from other specialties who are (children of) migrants reported significantly more often that they experienced differences on ethnic and/or cultural levels with their supervisors than residents of Dutch origin. Conclusion While (children of) migrants were underrepresented in this cohort, especially given the demographic distribution of the region of Rotterdam, a comparison of our results with previously published census data on medical students cohorts indicates no substantial loss of ethnic diversity in the transition from medical student to residency. Yet, these groups scored lower on questions related to sense of belonging. Clinical trial number Not applicable.